Hill-forts of Northern France - Wheeler, Sir, Mortimer (Reports of the Research Committee of the Society of Antiquaries of London, 1957)
This is an account of the excavations at several hill-forts in Northern France, undertaken in 1938 and 1939. Included are descriptions of human remains and artefacts such as pottery, coins, weaponry and metalwork, together with an account of the methodology used to unearth these.